Strengthening the Halal Industry Ecosystem through Halal Certification, Product Literacy, Awareness, and Promotion: Moderating Role of Islamic Financing - Rizky Nur Ayuningtyas Putri; Zakky Fahma Auliya; Agung Novianto Margarena; Rowiyah Asengbaramae (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the influence of halal certification, halal product literacy, halal awareness, and promotional efforts on the development of the halal industry ecosystem, with Islamic financing as a moderating variable. It adopts Ecosystem Innovation Theory to explain collaboration among government, producers, and Islamic financial institutions.Method: This explanatory quantitative study involved 400 halal-certified MSME actors in the Soloraya region, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with SEM-PLS to examine direct and moderating effects.Result: The findings indicate that halal certification, halal product literacy, and promotional efforts have positive and significant effects on the halal industry ecosystem. Halal awareness does not show a significant direct effect. Islamic financing significantly moderates the relationship between halal awareness and the halal industry ecosystem, but it does not moderate the relationships involving halal certification, halal product literacy, or promotional efforts.Practical Implications for Economic Growth and Development: The study emphasizes the need for integrated collaboration among MSMEs, government, and Islamic financial institutions. MSMEs should strengthen certification compliance, halal education, and digital promotion. The government should provide regulatory support, certification subsidies, and halal literacy infrastructure. Islamic financial institutions should design financing products that align with halal-certified MSME needs.Originality/Value: This study extends Ecosystem Innovation Theory in halal industry research by positioning Islamic financing as a moderator. It offers a new perspective on how Islamic financing strengthens the link between halal awareness and halal ecosystem development.